2021
DOI: 10.1021/acs.jpca.1c07523
|View full text |Cite
|
Sign up to set email alerts
|

Positional and Conformational Isomerism in Hydroxybenzoic Acid: A Core-Level Study and Comparison with Phenol and Benzoic Acid

Abstract: Three positional isomers of hydroxybenzoic acid, as well as phenol and benzoic acid, were studied using core-level photoemission and X-ray absorption spectroscopies, supported by quantum chemical calculations. While 2-hydroxybenzoic (salicylic) acid exists as a single conformer with an internal hydrogen bond, 3and 4-hydroxybenzoic acids are mixtures of multiple conformers. The effects due to isomerism are clearly seen in the C 1s and O 1s photoelectron spectra, whereas the conformational effects on the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The present calculated VIE of AB at 10.57 eV agrees well with the measurements which are between the two experimental measurements of 10.58 eV and 10.00 eV . In addition, our recent joint XPS experimental and theory study of hydroxybenzoic acids revealed that the vibrational impact is small for fast ionization processes so that in the present study, only the first-order VIEs are considered. In addition, the fact that only the first IE available without any higher valence IEs of the boron–nitrogen hydrides also makes such high level calculations less useful.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The present calculated VIE of AB at 10.57 eV agrees well with the measurements which are between the two experimental measurements of 10.58 eV and 10.00 eV . In addition, our recent joint XPS experimental and theory study of hydroxybenzoic acids revealed that the vibrational impact is small for fast ionization processes so that in the present study, only the first-order VIEs are considered. In addition, the fact that only the first IE available without any higher valence IEs of the boron–nitrogen hydrides also makes such high level calculations less useful.…”
Section: Resultssupporting
confidence: 90%
“…To further study the electronic structure and their behavior of these compounds may require information of other properties such as excitations of both valence and core electrons. As such, recent synchrotron sourced X-ray techniques including near-edge X-ray absorption fine structure (NEXAFS) enables an unambiguous identification of fingerprints for elements in molecules and core excitation spectra . It will be interesting to use new measured NEXAFS of the boron–nitrogen hydrides in the near future to benchmark the existing extended second-order algebraic–diagrammatic construction approximation scheme for polarization propagator ADC(2)­x , against the recently developed coupled-cluster (CC) theory obtained from a new time-dependent formalism based (EOM-CCSDT) and quadruples (EOM-CCSDTQ) , for core excitation spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Recent joint CMS and XPS studies reveal that intramolecular hydrogen bonding (OÁ Á ÁH) deeply impacts to core electrons (O1s) of molecules. 63 Combining the measured O1s XPS (for hydrogen acceptor) and 1 H-NMR (for hydrogen donor) with quantum mechanics, intramolecular hydrogen bonding (OÁ Á ÁH) of molecules can be studied locally. 64 In addition, XPS provides core electron ionization of a molecule which localised on specific atoms.…”
Section: Photoelectron Spectroscopy and Electron Momentum Spectroscopymentioning
confidence: 99%
“…The rotamer aspirin3 contains an internal hydrogen bond between the carboxylic acid hydrogen and the ether-like oxygen bonded to the acetyl group. Often internal hydrogen bonds are found in the lowest energy conformer [35][36][37][38] of a molecule, but in this case the two lowest energy forms do not form an internal hydrogen bond. As noted above, this has been attributed 7 to the stabilization of the lower energy forms by the Bu ¨rgi-Dunitz trajectory.…”
Section: Results: Conformersmentioning
confidence: 99%